Collaborative Skills Profile Students of Satya Wacana Christian Middle School Grade VII on the Material of Classification of Living Things - Natalia Rosa Keliat; Herlintho Bayadat Luturmas; Susanti Pudji Hastuti (UNIVERSITAS PGRI MADIUN, 2026)
The aim of the study is to determine the collaborative skills of seventh grade students of Satya Wacana Christian Middle School on the material of classification of living things. The study used a quantitative descriptive method. The subjects were all seventh grade students of Satya Wacana Christian Middle School of 60 peoples using a purposive sampling technique. Data collection techniques used are: 1) observation techniques using collaborative skills observation sheet instruments with indicators including: working productively; being responsible, respecting other students and compromising; 2) teacher interviews to find out problems related to student collaboration and the learning methods used. The data analysis technique used to determine the differences in collaborative skills of students in grade VII was using percentage techniques. The results of the study obtained collaborative skills of students with the beginner category reaching 11.7%, the basic category reaching 43.3%, the proficient category reaching 45% and no students reaching the exemplary category. Based on the four indicators of collaborative skills, the indicator of respecting other students achieved the best results with the proficient category, and the exemplary category reaching 88.3%. Students achieved the responsible indicator with the proficient category,the exemplary category reaching 78.3%, the indicator of working productively with the proficient category, and the exemplary category reaching 68.3%. Furthermore the indicator of compromising with the proficient category, and the exemplary category reaching 46.7%.